2015
DOI: 10.1089/dna.2015.2951
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Crocin on Cell Cycle Regulators in N-Nitroso-N-Methylurea-Induced Breast Cancer in Rats

Abstract: We previously showed the anticancer effect of crocin, a saffron carotenoid, in both breast and gastric cancers in animal models, but its mechanism of action is not clearly known, yet. In this study, the effect of crocin on cell cycle regulators is investigated. Female Wistar Albino rats were divided into two groups, with or without N-nitroso-N-methylurea (NMU) injection. After tumor formation, each group of rats was divided into two subgroups, receiving crocin or vehicle only. After 5 weeks, the rats were sacr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 50 publications
0
28
0
Order By: Relevance
“…In agreement with this study, blocking Wnt activity can be considered as a strategy to reverse the drug-sensitivity of CD133-positive cells to 5-FU. 49 Zhao et al 50 have also reported the potential activity of crocin in the downregulation of cyclin D1 in bladder cancer. 48 In a study on N-nitroso-Nmethylurea-induced breast cancer in rats, crocin induced cell cycle arrest via suppression of cyclin D1.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with this study, blocking Wnt activity can be considered as a strategy to reverse the drug-sensitivity of CD133-positive cells to 5-FU. 49 Zhao et al 50 have also reported the potential activity of crocin in the downregulation of cyclin D1 in bladder cancer. 48 In a study on N-nitroso-Nmethylurea-induced breast cancer in rats, crocin induced cell cycle arrest via suppression of cyclin D1.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main activities by Crocin is a change in the expression of genes related in the redox system of cells such as GST, GPx, CAT, and SOD. In addition to changes in gene expression levels, interactions with cellular enzymes including SOD proteins or peroxidase have also been reported to induce the antioxidant activity of Crocin . Another mechanism underlying the antioxidant activity of Crocin is the alteration of the stress marker genes in the ER system.…”
Section: Molecular Mechanism Of Antioxidant Activity Of Crocinmentioning
confidence: 99%
“…In addition to changes in gene expression levels, interactions with cellular enzymes including SOD proteins or peroxidase have also been reported to induce the antioxidant activity of Crocin. 10,13,29,61 Another mechanism underlying the antioxidant activity of Crocin is the alteration of the stress marker genes in the ER system. Genes related to ER oxidative stress markers, whose expression is modulated by the Crocin are XBP-1/s, BiP, PERK, and CHOP.…”
Section: Molecular Mechanism Of Antioxidant Activity Of Crocinmentioning
confidence: 99%
“…Interestingly, crocin exhibited no significant effect on the growth of noncancerous cells . Moreover, several in‐vivo studies have showed the anticancer effect of crocin on various cancers such as breast and gastric tumours in animal models …”
Section: Molecular Mechanisms Of Anticancer Effects Of Crocinmentioning
confidence: 99%
“…Changes in the level of mRNA expression and enzyme activity of the genes in the cellular redox system including glutathione S‐transferase (GST), glutathione peroxidase (GPx), catalase and superoxide dismutase (SOD) are considered as remarkable mechanisms. Rather than expression changes of the genes, various mechanisms of action were reported to be related with the antioxidant effect of saffron extracts such as interaction with enzymes (SOD proteins, peroxidases) or signal transduction compartments of free radicals in the monocytes and direct suppression of ROS through interaction of a wide variety of proteins with antioxidant compounds . Moreover, endoplasmic reticulum (ER) is closely linked to oxidative stress status of the cells; the transcriptional level changes of the ER stress markers XBP‐1/s, BiP, PERK and CHOP are responsible for many stress‐induced diseases including cancer.…”
Section: Molecular Mechanisms Of Anticancer Effects Of Crocinmentioning
confidence: 99%